One response: Global Outbreak Alert and Response Network supporting the COVID-19 response, Kiribati - Laurie, Louise; Leong, Margaret; Titaake Kaufusi, Toata; Murdoch, Helen; Snowdon, Wendy; Salmon, Sharon; Zimmerman, Peta-Anne (Western Pacific Surveillance and Response, 2024)
Problem: In January 2022, Kiribati experienced widespread community transmission of COVID-19, leading to high rates of infection among health-care workers (HCWs), which reduced essential HCWs during a period of increased hospital admissions.Context: Kiribati, a Pacific island country made up of a remote group of 33 low-lying atolls in the Pacific Ocean, experienced its first surge of COVID-19 cases beginning on 24 January 2022.Action: Reports of increasing numbers of COVID-19 cases in South Tarawa prompted the Kiribati Ministry of Health and Medical Services to request assistance from the international community, including the World Health Organization’s Global Outbreak Alert and Response Network (GOARN), to support national COVID-19 response operations. Specialists in infection prevention and control (IPC) were deployed to Kiribati in February 2022 to assist the Ministry’s National COVID-19 Taskforce in collaboration with national partners. These specialists helped review and strengthen IPC capacities to accommodate a potential patient surge and consequent demands for medical consumables in health-care facilities in South Tarawa.Outcome: Strengthened knowledge about and processes for IPC among HCWs prevented health care-associated infections and reduced community disease transmission during the first surge of COVID-19 cases in Kiribati.Discussion: GOARN has the capacity and ability to rapidly deploy experts to support requests for assistance. Outbreak response activities can be enhanced and sustained by using GOARN’s resources and collaborating with all partners, as necessary.
Keywords: infection prevention and control; outbreak response; COVID-19; GOARN; Kiribati; Pacific islands